Oligogenic Inheritance of Monoallelic TRIP11, FKBP10, NEK1, TBX5, and NBAS Variants Leading to a Phenotype Similar to Odontochondrodysplasia - Costantini, Alice; Valta, Helena; Suomi, Anne-Maarit; Mäkitie, Outi; Taylan, Fulya (Frontiers in Genetics, 2021)
Skeletal dysplasias are often well-characterized and only a minority of the cases remain unsolved after a thorough analysis of pathogenic variants in over 400 genes that are presently known to cause monogenic skeletal diseases. Here we describe an 11-year-old Finnish girl, born to unrelated healthy parents, who had severe short stature and a phenotype similar to odontochondrodysplasia (ODCD), a monogenic skeletal dysplasia caused by biallelic TRIP11 variants. The family had previously lost a fetus due to severe skeletal dysplasia. Exome sequencing and bioinformatic analysis revealed an oligogenic inheritance of a heterozygous nonsense mutation in TRIP11 and four likely pathogenic missense variants in FKBP10, TBX5, NEK1 and NBAS in the index patient. Interestingly, all these genes except TBX5 are known to cause skeletal dysplasia in autosomal recessive manner. In contrast, the fetus was found homozygous for the TRIP11 mutation and achondrogenesis type IA diagnosis was thus molecularly confirmed, indicating two different skeletal dysplasia forms in the family. To best of our knowledge, this is the first report of an oligogenic inheritance model of a skeletal dysplasia in a Finnish family. Our findings may have implications for genetic counseling and for understanding the yet unsolved cases of rare skeletal dysplasias.